Residential Electricity Subsidies in Pakistan : Targeting, Welfare Impacts, and Options for Reform - Walker, Thomas (World Bank, Washington, DC, 2017)
This paper examines the economic and social implications of the current system of residential electricity subsidies in Pakistan, and assesses the potential to improve the system's outcomes through alternative targeting and program design. The analysis is multi-disciplinary in nature, drawing on national household survey data, electric company data on household electricity consumption, a welfare database, and a specially commissioned qualitative assessment of household and service provider attitudes and experiences. Affordability is only one of many concerns among electricity users, with reliability of supply and customer service being arguably more important. The analysis finds that targeting could be improved considerably by allocating subsidies according to proxy-means test scores using an existing national proxy-means test database. Providing a flat credit rather than a price subsidy could also alleviate certain governance concerns. The paper concludes with some guidance on how to carry out these reforms based on international experience.